2001
DOI: 10.1174/021347401317351152
|View full text |Cite
|
Sign up to set email alerts
|

El perfil psicosocial del emprendedor: un estudio desde la perspectiva de los valores

Abstract: Por una parte, realizamos una reflexión sobre las posibilidades que ofrece el marco teórico del Modelo de Schwartz (1992) al estudio de la conducta emprendedora y, por otra parte, exploramos de manera empírica los valores personales dentro de las dimensiones de Individualismo y Colectivismo que favorecen dicha conducta. Para ello, hemos realizado un estudio descriptivo comparando los diferentes tipos de valores y los valores específicos entre un grupo de sujetos emprendedores y otro grupo que no lo son. Los re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
30

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 12 publications
1
31
0
30
Order By: Relevance
“…Spanish university graduates whose priorities are openness to change and self-enhancement values do exhibit higher intention to become entrepreneurs, as hypotheses H1 and H3 stated. This is in accordance with previous studies that identified individualistic values such as power, achievement, hedonism, stimulation and self-direction to predict the entrepreneurial intention Moriano, et al, 2001;Polley, et al, 1988). However, the results did not support H2 and H4.This could point out to the existence of more complex relationships between the values themselves, and between values and intentions.…”
Section: Discussionsupporting
confidence: 93%
“…Spanish university graduates whose priorities are openness to change and self-enhancement values do exhibit higher intention to become entrepreneurs, as hypotheses H1 and H3 stated. This is in accordance with previous studies that identified individualistic values such as power, achievement, hedonism, stimulation and self-direction to predict the entrepreneurial intention Moriano, et al, 2001;Polley, et al, 1988). However, the results did not support H2 and H4.This could point out to the existence of more complex relationships between the values themselves, and between values and intentions.…”
Section: Discussionsupporting
confidence: 93%
“…The EIQ measures PBC through entrepreneurial self-efficacy in line with other research on entrepreneurial intentions (Krueger et al, 2000;Kolvereid & Isaksen, 2006;Moriano, 2005;van Gelderen et al, 2008). In this study, we used a six-item entrepreneurial selfefficacy scale.…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…In their review of TPB, Armitage and Conner (2001) conclude that self-efficacy is more clearly defined and more strongly correlated with intentions than PBC. In fact, self-efficacy has replaced PBC in numerous studies (Krueger et al, 2000;Kolvereid & Isaksen, 2006;Moriano, 2005;van Gelderen et al, 2008), and a recent meta-analysis showed that it is strongly positively related to business creation and entrepreneurial success (Rauch & Frese, 2007).…”
Section: Theory Of Planned Behavior (Tpb) Explaining Entrepreneurial mentioning
confidence: 99%
See 1 more Smart Citation
“…Según Moriano, Trejo & Palací (2001) los emprendedores son portadores de competencias como: adaptabilidad, autonomía, capacidad de asumir riesgos, innovación, proactividad y tolerancia a la incertidumbre.…”
Section: El Enfoque De Los Rasgos De Personalidadunclassified